2023
DOI: 10.5603/demj.a2023.0010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of factors related to emergency re-referral in patients with heart failure a hospital in Tehran — Iran: a cross-sectional study

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Its prevalence in adult and child populations is increasing alarmingly, with serious public health implications [4]. According to the World Health Organization (WHO), up to 13% of the world's population struggles with obesity [5] Several studies have shown that obesity affects both the risk of CVD (such as hypertension, coronary heart disease, and heart failure) and increased complications in people with these conditions [6][7][8][9]. On the other hand, some studies have shown that obesity does not affect the outcome of patients following CA [10].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence in adult and child populations is increasing alarmingly, with serious public health implications [4]. According to the World Health Organization (WHO), up to 13% of the world's population struggles with obesity [5] Several studies have shown that obesity affects both the risk of CVD (such as hypertension, coronary heart disease, and heart failure) and increased complications in people with these conditions [6][7][8][9]. On the other hand, some studies have shown that obesity does not affect the outcome of patients following CA [10].…”
Section: Introductionmentioning
confidence: 99%